Implementasi Nilai-Nilai Kewarganegaraan Dalam Menghadapi Perubahan Sistem Blok Di Universitas Negeri Medan - Putri Seruni; Pradipa Nasywa Syukri; Theressa Saota; Neha Damora Siregar (PT. Intelek Cendikiawan Nusantara, 2024)
This study aims to analyze the implementation of civic values in addressing the transition to a block system at Universitas Negeri Medan. The block system is a learning approach that condenses the academic workload within a specific timeframe, requiring quick adaptation from both students and faculty. This research employed both qualitative and quantitative methods with a case study approach. Data were collected through questionnaires distributed to students enrolled in the Civic Education course at Universitas Negeri Medan. The findings reveal that civic values such as cooperation, tolerance, and responsibility are well-implemented in the block system, with 83% of students agreeing that the system enhances the quality of civic education. However, the main challenges identified include high academic workloads and limited time for extracurricular activities, making it difficult for some students to adjust. The study recommends further collaboration between lecturers and students in building a practice community focused on civic education, and providing more opportunities for character development activities.